Does Socioeconomic Diversity Make a Difference? Examining the Effects of Racial and Socioeconomic Diversity on the Campus Climate for Diversity. (June 2013) - Park, Julie J.; Denson, Nida; Bowman, Nicholas A.
This article considers whether the socioeconomic diversity of the undergraduate student body and experiences with cross-class interaction (CCI) are significantly related to cross-racial interaction (CRI) and engagement with curricular/co-curricular diversity (CCD) activities. Individual students who reported higher levels of CCI had significantly higher levels of CRI and CCD. While the socioeconomic diversity of the student body had no direct effect on student involvement in CCD activities or CRI, it had an indirect effect on these activities via CCI. In other words, a socioeconomically diverse institution is associated with more frequent interactions across class lines, which is associated both with more frequent interactions across race and greater involvement in CCD activities. Findings indicate that both socioeconomic and racial diversity are essential to promoting a positive campus racial climate and that racial and socioeconomic diversity, while interrelated, are not interchangeable. Implications for the campus climate for diversity are discussed.